The turn of the soul : representations of religious conversion in Early Modern art and literature - Stelling, Lieke; Hendrix, Harald; Richardson, Todd (Intersections (Boston, Mass.) ;, 2012)
Focusing on conversion as one of early modern Europe's most pressing issues, the present book offers a comprehensive reading of artistic and literary ways in which spiritual transformations and exchanges of religious identities were given meaning.